Evaluation of sulphation baking and autogenous leaching behaviour of Turkish metallurgical slag flotation tailings - UZUN KART, ELİF (OFICYNA WYDAWNICZA POLITECHNIKI WROCLAWSKIEJ, 2021)
Turkish metallurgical slag flotation tailing's (MSFT) that has not been evaluated yet sulphation baking phase transformations and autogenous leaching behaviour were investigated. The MSFT in the study consists of the residual fayalite (FeO center dot SiO2) phase from the flotation, with a copper recovery of 87%, of the slag released during the smelting of the copper sulphide mine in northern Turkey, and the non-soluble glassy/amorphous structure containing the 0.34 % Cu, 4.16% Zn and 0.15 % Co base metals locked and doped to this phase. The effects of temperature (350 -650 degrees C) and sulphuric acid dosages (4-10 ml) on sulphation baking were investigated by X-ray diffraction and sulphur analyses of the baked MSFT (B-MSFT) to produce soluble base metal sulphates. Since sulphated metals are a kind of metal salt, autogenous leaching was applied to the B-MSFTs only with purified water to dissolute copper, zinc and cobalt. X-ray diffraction patterns show the transformation of fayalite to oxide and sulphate phases due to sulphation baking. All dissolution values of Co and Zn obtained by autogenous leaching of B-MSFTs produced under all determined conditions are almost the same as one another. This indicates that Co and Zn are doped to fayalite together and that part of cobalt is doped to the zincite structure and liberated and sulphated together. This study showed that MSFTs decompose leading to liberation and sulphation of the doped base metals in its structure at a rate of >= 90%, and that they autogenously dissolve under atmospheric conditions leading to recovery in a simple and economic manner.
Keywords: copper smelter slag; flotation tailings; sulphation baking; autogenous leaching; base metals extraction; COPPER SLAG; METAL VALUES; RECOVERY; EXTRACTION